Pengembangan Minuman Kedelai Hitam untuk Ibu Menyusui - Pramitasari, Rianita (Program Studi Teknologi Pangan, 2017)
Genistein and daidzein could stimulate the prolactin hormone that play a role in breastmilk production. Black soybean contain genistein and daidzein which has a potent to developed as the functional food for breastfeeding mothers. The purpose of this study was to get the optimal formula, determine the nutritional value, and genistein and daidzein contents of black soybean beverage. The beverages were made from 5 variations of time soaking (0, 3, 6, 9, and 12 hours). Further analysis of sensory and nutritional value from the beverages. The results showed that the beverage with 12 hours time soaking was the most preferred beverage by panelists. One serving (150 ml) of selected beverage was able to supply 3.65% of carbohydrate needs; 4.75% of protein needs; 3.33% of fat needs; and 3.68% of total energy based on Recommended Dietary Allowance of Indonesian breastfeeding mother per day. It contained 2.78 ± 0.25 mg/g of genistein and 0.087 ± 0.13 mg/g of daidzein.